The role of standardized patient assessment forms in medical communication skills education - Grace Peters (Qualitative Research in Medicine & Healthcare)
Communication skills training is a routine practice in medical education designed to instruct and evaluate future physicians in matters of patient-provider interaction. Based on the United States Medical Licensing Examination Step 2 Clinical Skills (CS), medical schools across the United States hire and train standardized patients (SPs) to act as patients in and evaluators of simulated interactions with medical students (MSs). Using discourse analysis, I examine how a computerized assessment form creates a particularized version of communication skills with implications for future practice. The 39-item checklist is completed by SPs following a simulated interaction designed to prepare third-year MSs for the Step 2 CS. Specifically, I analyze how the form is structured to make recognizable specific communication skills tasks, who should complete said tasks, and what varying degrees of communication skills competency are within the realm of task completion. By analyzing the form, I consider the agency of texts in medical education, the implications of technologizing communication as an institutional skill, and the limitations of enlisting SPs to evaluate communication skills competency under the guise of a patient perspective.